Age and biorhythm-related changes in autonomous and hormone regulation among arterial hypertension patients - V. R. Vebe; M. S. Kazymov; M. N. Kopina (Российский кардиологический журнал)
Inpatients with arterial hypertension, changes in absolute parameters of autonomous (and hormone, in women) activity were accompanied by development of age and biorhythm-related (circadian, menstrual cycles) desynchronosis between sympathetic nervous system, adrenoreceptor density, and sex hormone levels.